A critical hermeneutic circle to reimagine professional selfhood - Maykut, Colleen; Miller, Cole; Porter, Meredith; Badu, Nikki; Barroma, Arianne; Cheung, Chanel; McLeod, Danielle; Trotter, Cassidy (My University, 2023)
Professional selfhood (PSH) is the embodiment of an individual’s social location influenced by being in and with the world. PSH informs our evolving professional journey as nurses. As our journeys are never singular, community formation to support this evolution is vital. Utilizing body mapping as an aesthetic methodology was enhanced through reflexivity situated in a critical hermeneutic circle. The phenomenon of interest in the original research study of six novice nurses was how the tension between what they desire to do and what they were able to do, lived in and on their bodies. This is our story, as a community of artists and researchers, who were inspired by a Critical Hermeneutic Circle the ongoing nurturance to enter this brave space to re-imagine our evolving PSH.
Keywords: aesthetic; experience; halldorsdottir; nurse; professional